Functional verification of GhAFP8 in upland cotton under verticillium wilt stress - Ting Zhou; Peilin Wang; Jianglin Xu; Dong Liang; Yejun Yang; Yongqiang Wang; Yuanchun Pu; Guoli Zhang; Jinling Huang; Guoqing Sun (Plant Stress, 2024)
Verticillium wilt, caused by Verticillium dahliae, poses a severe threat to cotton growth and yield as a soil-borne disease. The ABI five binding protein (AFP) family, characterized by alkaline leucine zip-like transcription factors, responds to ABA signals, and its expression is induced by ABA as well as various biological and abiotic stresses. In this study, we identified 23 members of the four cotton AFP families, revealing high conservation in both gene and protein structures. Collinearity analysis indicated a closer relationship between GhAFPs and AtAFPs than rice. Cis-element analysis of the cotton AFP promoters unveiled elements associated with plant hormones, abscisic acid, abiotic stress, and light response. To unravel the role of the cotton AFP family in verticillium wilt resistance, we pinpointed a highly expressed gene, GhAFP8, from a resistant variety by monitoring expression levels pre- and post-inoculation for each family gene. Subcellular localization confirmed nuclear localization for GhAFP8. Overexpression of GhAFP8 in tobacco demonstrated enhanced resistance to Verticillium dahliae compared to wild-type plants. Further functional exploration utilizing the VIGs system in cotton revealed that silencing the GhAFP8 gene compromised cotton's resistance to Verticillium dahliae. Transcriptome analysis 72 hours post-inoculation in TRV::00 plants and TRV::GhAFP8-silenced plants showed that GhAFP8 silencing primarily impacts the abscisic acid-activated signaling pathway, MAPK signaling pathway, plant hormone signal transduction, and the activation of plant-pathogen interaction pathway. Additionally, GhAFP8 exhibited responsiveness to signals from jasmonic acid (JA), abscisic acid (ABA), and salicylic acid (SA). In summary, we demonstrated the active role of the GhAFP8 gene in conferring resistance to Verticillium dahliae, positioning it as a promising candidate for cotton breeding against verticillium wilt.